2023
DOI: 10.2807/1560-7917.es.2023.28.3.2200195
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events following first and second dose COVID-19 vaccination in England, October 2020 to September 2021: a national vaccine surveillance platform self-controlled case series study

Abstract: Background Post-authorisation vaccine safety surveillance is well established for reporting common adverse events of interest (AEIs) following influenza vaccines, but not for COVID-19 vaccines. Aim To estimate the incidence of AEIs presenting to primary care following COVID-19 vaccination in England, and report safety profile differences between vaccine brands. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In Domain III ( informing about health interventions ), we are able to infer the impact of interventions, such as lockdowns and shielding, during the COVID-19 pandemic, and we can see from our data the impact of school closures [ 62 , 63 ]. We are strong in measuring vaccine uptake and effectiveness, and our data have been used for vaccine adverse events [ 60 , 64 ]. We only have limited abilities to assess the effectiveness of some antivirals and other therapeutics owing to their central administration, and our capabilities are greater where these are recorded in the GP CMR.…”
Section: Resultsmentioning
confidence: 99%
“…In Domain III ( informing about health interventions ), we are able to infer the impact of interventions, such as lockdowns and shielding, during the COVID-19 pandemic, and we can see from our data the impact of school closures [ 62 , 63 ]. We are strong in measuring vaccine uptake and effectiveness, and our data have been used for vaccine adverse events [ 60 , 64 ]. We only have limited abilities to assess the effectiveness of some antivirals and other therapeutics owing to their central administration, and our capabilities are greater where these are recorded in the GP CMR.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, our data indicated that adverse reactions resulting from heterologous boosting with Ad5-nCoV after three-dose priming with an inactivated SARS-CoV-2 vaccine were predictable and manageable, although they presented with a higher incidence than those induced by homologous boosting with an inactivated vaccine. Tsang et al demonstrated that incidences of adverse reactions decreased with the frequency of vaccination 28 . This may also be a result of the monitoring sensitivity, as adverse reactions were reported in 25.3% of participants that received inactivated SARS-CoV-2 vaccine in our study, a higher percentage than seen in other homologous booster studies 29 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been used for influenza and respiratory disease monitoring for the last 50 years [23]. During the COVID-19 pandemic, with linkage to existing NHS England datasets, RSC data were also used to understand its epidemiology and assess vaccine effectiveness and safety [24][25][26][27]. This modified version of the CMMS was used to assess the real-world effectiveness of the Oxford-AstraZeneca Covid-19 Vaccine in England (RAVEN) study, which was run on the RSC using linked data from NHS England [28].…”
Section: Introductionmentioning
confidence: 99%